Bulk atmospheric deposition of persistent organic pollutants and polycyclic aromatic hydrocarbons in Central Europe - Nežiková, Barbora; Degrendele, Céline; Čupr, Pavel; Hohenblum, Philipp; Moche, Wolfgang; Prokeš, Roman; Vaňková, Lenka; Kukučka, Petr; Martiník, Jakub; Audy, Ondřej; Přibylová, Petra; Holoubek, Ivan; et al. (Environmental science and pollution research international, 2019)
Polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs) and organochlorine pesticides (OCPs) are ubiquitous and toxic contaminants. Their atmospheric deposition fluxes on the regional scale were quantified based on simultaneous sampling during 1 to 5 years at 1 to 6 background/rural sites in the Czech Republic and Austria. The samples were extracted and analysed by means of gas chromatography coupled to mass spectrometry. For all seasons and sites, total deposition fluxes for Σ15PAHs ranged 23-1100 ng m-2 d-1, while those for Σ6PCBs and Σ12OCPs ranged 64-4400 and 410-7800 pg m-2 d-1, respectively. Fluoranthene and pyrene were the main contributors to the PAH deposition fluxes, accounting on average for 19% each, while deposition fluxes of PCBs and OCPs were dominated by PCB153 (26%) and γ-hexachlorobenzene (30%), respectively. The highest deposition flux of Σ15PAHs was generally found in spring, while no seasonality was found for PCB deposition. For deposition fluxes for Σ12OCPs, no clear spatial trend was found, confirming the perception of long-lived regional pollutants. Although most OCPs and PCBs hardly partition to the particulate phase in ambient air, on average, 42% of their deposition fluxes were found on filters, confirming the perception that particle deposition is more efficient than dry gaseous deposition. Due to methodological constraints, fluxes derived from bulk deposition samplers should be understood as lower estimates, in particular with regard to those substances which in ambient aerosols mostly partition to the particulate phase.
Keywords: Pesticides; Bulk atmospheric deposition; Environmental Monitoring; hexachlorbenzen; pesticidy; polychlorované bifenyly; Rakousko; monitorování životního prostředí; OCPs; Česká republika; chlorované uhlovodíky; POPs; Europe; plynová chromatografie s hmotnostně spektrometrickou detekcí; Polychlorinated Biphenyls; Hexachlorobenzene; Hydrocarbons, Chlorinated; polycyklické aromatické uhlovodíky; Central Europe; látky znečišťující vzduch; Gas Chromatography-Mass Spectrometry; Deposition fluxes; Czech Republic; Evropa; PCBs; PAHs; Austria; Polycyclic Aromatic Hydrocarbons; Air Pollutants